2018
DOI: 10.1590/abd1806-4841.20186228
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent aphthous ulceration: an epidemiological study of etiological factors, treatment and differential diagnosis

Abstract: BACKGROUNDRecurrent aphthous ulcerations are common benign ulcerated lesions on the mouth, whose etiology is poorly understood, with controversial treatment and difficult to control in clinical practice.OBJECTIVETo evaluate the cases of recurrent aphthous ulcerations with a focus on treatment, diagnosis and etiology.METHODSThis is a retrospective study of the cases of the Oral Diagnosis service of the Rio Grande do Norte Federal University in Natal/RN. Data such as sex, age, race, location, smoking habits, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 17 publications
2
39
0
3
Order By: Relevance
“…There is a small number of studies in which patients were diagnosed by direct detection of present lesions by a practitioner. Queiroz et al [22] A similar negative correlation between smoking and RAS was noticed in our study. The treatment and, many times, the diagnosis of RAS are a challenge in the daily life of the clinician.…”
Section: Original Articlessupporting
confidence: 91%
“…There is a small number of studies in which patients were diagnosed by direct detection of present lesions by a practitioner. Queiroz et al [22] A similar negative correlation between smoking and RAS was noticed in our study. The treatment and, many times, the diagnosis of RAS are a challenge in the daily life of the clinician.…”
Section: Original Articlessupporting
confidence: 91%
“…Recurrent aphthous stomatitis (RAS) is an inflammatory condition resulting in painful ulcerations on the oropharyngeal mucosa, and is thought to affect approximately 1.6% of the general population. [168] Three studies reported prevalence of RAS among individuals with SIgAD, finding values from 1.2% to 4.9%, with a weighted average of 2.4%. [20,28,128] (Table 24) However, RAS is associated with other autoimmune disorders including Celiac disease and inflammatory bowel disease, and may be a manifestation of these diseases in some cases.…”
Section: Recurrent Aphthous Stomatitismentioning
confidence: 99%
“…[20,28,128] (Table 24) However, RAS is associated with other autoimmune disorders including Celiac disease and inflammatory bowel disease, and may be a manifestation of these diseases in some cases. [168] Without controlling for these disease entities, it is impossible to determine whether RAS has a separate correlation with SIgAD.…”
Section: Recurrent Aphthous Stomatitismentioning
confidence: 99%
“…This high prevalence in women can be explained by thefact that women seek more medical attention. 7 Although several etiologic factors have been proposed, the exact causes of recurrent aphthous stomatitis are still not very clear. Previous studies of tissue infiltrated mononuclear cells in recurrent aphthous stomatitis specimens favor the role of cellmediated cytotoxicity in its immunopathogenesis.…”
Section: Discussionmentioning
confidence: 99%